Non-biodegradable microplastics in soils: A brief review and challenge - Zhang, Shaoliang; Wang, Jiuqi; Yan, Pengke; Hao, Xinhua; Xu, Bing; Wang, Wan; Aurangzeib, Muhammad (Journal of hazardous materials, 2021)
Non-biodegradable microplastics (MPs) pollution long-termly existed in soils, and was only concerned in recent years. In order to better understand MP behavior in soils, the sources, migration, distribution, biological effects, degradation and analytical methodology of non-biodegradable MPs in soils were quantificationally summarized from 170 publications based on Web of Science in 1950–2020. From the publications, we found these studies were mainly carried out in the Asia (60.0%) and Europe (23.3%), and most were on agricultural soils (68.5%). Polyethylene-MP (78.8% of the studies), Polypropylene-MP (78.8%), and Polystyrene-MP (45.5%) were the MPs most frequently found in the soils, with a MP size of 20–5000 µm being most common. Of the soil samples 64.3% contained MP 1000–4000 items kg-1, and the colour frequency ranking is blue (66.7%) > white (61.1%) ≈ red ≈ black. MPs changed the soil microenvironment and microorganism activity, and caused the negative effects on both soil animals (100%) and plants (57.9%). MP degradation was influenced by the photooxidation reactions, microorganism activities, enzymatic effects, environmental conditions, and by the composition, size and morphology of the MPs. An optional analytical method was suggested in this study. At the end of paper, the urgent and important research work in the future was prospected. [Display omitted] •PE-MP, PP-MP, PS-MP with blue, white, red, black were most frequently found in soils.•MPs of 1000–4000 items kg−1 at size of 20–5000 µm took of 50% of soil samples.•MPs caused the negative effects on both soil animals (100%) and plants (57.9%).•An optional analytical method of soil MPs was suggested in this study.•Future prospects and challenging for follow up research have been discussed.